The Effect of Lifestyle on Social and Social Norm: A Case Study of Male University Students at a Public University in Banten, Indonesia - Lenny Wahyuningsih; Putri Dian Dia Conia; Meilla Dwi Nurmala; Aisling O’Boyle; Siti Muhibah; Bangun Yoga Wibowo (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
Developments in technology and culture affect a person's attitude and lifestyle. Lifestyle describes the